Percutaneous occluder device closure through femoral vein guidance by transthoracic echocardiography in adult atrial septal defect patients - Jia, Yixin (J Thorac Dis, 2018)
BACKGROUND: This study aimed to summarize percutaneous occluder device closure of atrial septal defects (ASD) through the femoral vein, using guidance by transthoracic echocardiography under local anesthesia without radiation or fluoroscopic guidance. METHODS: This was a case series of fourteen patients, 3 males and 11 females, diagnosed with central ASD, the diameter of the defect ranged from 9 to 32 mm, and the patients had no other heart malformations or organ dysfunction. The patients underwent a novel surgical technique of occluder device closure for ASD. The occluder closure procedures were completed through puncture of the femoral vein, and fluoroscopy-free catheter guidance by transthoracic echography without radiation. RESULTS: All of the cases had successful closure of the ASD, without residual shunt or complications. The median operation time was 18.7±22.5 min (range, 12–56 min), with no ICU-stay time and a short hospital stay of 2.3±0.5 days (range, 1–3 days). All patients were followed up for 2 years and there were no cases of residual shunt. All occluders remained in place. CONCLUSIONS: Percutaneous occluder device closure of ASDs through the femoral vein with fluoroscopy-free guidance by transthoracic echography without radiation under local anesthesia could be an easy choice for some simple ASD patients, and may also be favored by cardiac surgeons.